INFORMATION TECHNOLOGY IN THE MODERN ECONOMY - Omanov R. F. (Scholars Digest Publishing, 2023)
An innovative business model is a set of techniques and methods that a firm uses to design its business in accordance with its goals. An innovative business model is essentially a fundamental rethinking and radical redesign of business processes to achieve sharp, leap-like improvements in the main modern indicators of enterprise performance, such as cost, quality, service and pace.